2013
DOI: 10.1007/s00411-013-0496-3
|View full text |Cite
|
Sign up to set email alerts
|

Uranium distribution in broiler organs and possibilities for protection

Abstract: The aim of the present study was to investigate the distribution of uranium (uranyl nitrate hexahydrate, UN) in muscle and organs (kidney, liver, and brain) of broilers, after a 7-day contamination with UN and administration of two different adsorbents (organobentonite and organozeolite). The birds were contaminated during 7 days with 25 mg/UN per day. Adsorbents were given via gastric tube, immediately after contamination with UN. In group 1 that did not receive any adsorbents, histopathological changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Nearly 66 % of ingested uranium is deposited in the bones, the rest in the kidneys and liver, and a part is excreted by faces and urine 3. The results obtained by Mitrović et al [4] showed that in broilers uranium primarily accumulates in kidney and liver compared with brain and muscles.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Nearly 66 % of ingested uranium is deposited in the bones, the rest in the kidneys and liver, and a part is excreted by faces and urine 3. The results obtained by Mitrović et al [4] showed that in broilers uranium primarily accumulates in kidney and liver compared with brain and muscles.…”
Section: Introductionmentioning
confidence: 60%
“…In broilers after a 7-day contamination with 25 mg of uranyl nitrate hexahydrate per day, histopathological changes were observed in small intestine, liver, and kidney in the form of necrosis of intestinal villi, oedema and cytoplasmic vacuolation of hepatocytes, and dystrophic changes in the kidney tubules epithelium [4]. Results obtained in study on Beagle dogs indicated that through prolonged ingestion uranium was accumulated and distributed both in bone and bone marrow, saturation is reached only after about 10 years [14].…”
Section: Resultsmentioning
confidence: 99%
“…Also, the study of the activity concentrations in grain mixture, drinking water and soil particles ingested by poultry permits a better understanding of the main sources of each radionuclide and the calculation of concentration ratios and transfer coefficients for chicken meat and egg contents. Branislava et al (23) concluded that uranium in broilers primarily accumulates in kidney and liver compared with brain and muscles. Another study by Hassan ( 24) reported the elevation of uranium concentration in fish tissues ranging from 1.78 ± 0.19 μg/ kg -1 to 8.31 ± 0.51 μg/kg -1 when he compared between six common commercial species of Iraqi river fish.…”
Section: Oxidative -Antioxidative Stress Biomarkersmentioning
confidence: 99%